The Validity Ethnobotany Book of Jatropha gossypiifolia In The Coastal Forest Area Of Tabanio - Aulia Rahman; Dharmono Dharmono; Sri Amintarti (Master Program of Biology Education, Universitas Lambung Mangkurat, 2020)
One of the urgent problems in Ethnobotany learning is the lack of learning resources. Jatropha gossypiifolia is one of the plants found in the Tabanio Coastal Forest Area, Tanah Laut Regency, and has the potential to be used as a learning resource. The potency of the Jatropha gossypiifolia plant as a learning resource, teaching materials are made in the form of a scientific book on the study of ethnobotany Jatropha gossypiifolia plants in the Tabanio coastal forest as supporting material for the Ethnobotany course. This study aims to describe the validity of scientific books has developed by plant ethnobotany Jatropha gossypiifolia. This as supporting material for Ethnobotany courses. This study uses a research development method with the Education Design Research (EDR) model with a formative evaluation of the Tessmer test. This scientific book